Peran Mahasiswa PGMI Dalam Penguatan Materi Pronunciation Alfabet Melalui Media Flashcard di MIS Miftahul Huda II Kota Palangka Raya - Nurlaila Nurlaila; Zaitun Qamariah; Istiyati Mahmudah; Nuril Ainularifin; Milla Anggraini; Putri Cahya Novebriani; Deni Adi Saputra; Achmad Zaelani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This community service activity aims to improve the English alphabet pronunciation skills among students at MIS Miftahul Huda II in Palangka Raya City through the use of flashcard media. Students from the Elementary School Teacher Education (PGMI) program are actively involved in the planning, implementation, and evaluation of this program. The method used is a participatory approach, where PGMI students provide interactive learning using specially designed flashcards to help students recognize and correctly pronounce the alphabet. The results of this activity show a significant improvement in students' pronunciation skills and their enthusiasm for participating in the learning process. Additionally, the involvement of PGMI students in this program provides valuable practical experience in teaching and classroom management. Therefore, this activity is beneficial not only for the students but also for the professional competence development of PGMI students.